2018
DOI: 10.3390/soilsystems2030047
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Moments of Soil CO2 Efflux in a Water-Limited Grassland

Abstract: The metabolic activity of water-limited ecosystems is strongly linked to the timing and magnitude of precipitation pulses that can trigger disproportionately high (i.e., hot-moments) ecosystem CO2 fluxes. We analyzed over 2-years of continuous measurements of soil CO2 efflux (Fs) under vegetation (Fsveg) and at bare soil (Fsbare) in a water-limited grassland. The continuous wavelet transform was used to: (a) describe the temporal variability of Fs; (b) test the performance of empirical models ranging in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…The relatively small MAE of our model predictions may suggest generally well constrained Rs predictions at most pixels, while the relatively large RMSE may reflect the large prediction underestimations of extremely high observed Rs values (Figure a). Similar underestimation by machine learning approaches has been reported in models attempting to include hot moments of Rs in water limited ecosystems (Vargas et al, ) and for CO 2 and CH 4 fluxes in temperate forests (Warner et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…The relatively small MAE of our model predictions may suggest generally well constrained Rs predictions at most pixels, while the relatively large RMSE may reflect the large prediction underestimations of extremely high observed Rs values (Figure a). Similar underestimation by machine learning approaches has been reported in models attempting to include hot moments of Rs in water limited ecosystems (Vargas et al, ) and for CO 2 and CH 4 fluxes in temperate forests (Warner et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…While supplementing a temperature-based model with either θ or GEP terms increased the amount of explained variation in F soil to a similar degree, the combination of T s , θ, and GEP was required to maximize model performance and predict seasonality in F soil . Models that accounted for θ captured the pulsed increase in metabolic activity at the monsoon onset characteristic of semiarid ecosystems [12,21,63], whereas GEP terms improved the prediction of F soil magnitude and seasonality by reflecting the stimulating effect of photosynthesis on basal F soil ([39]; Figure 6). We found that F soil increased rapidly in response to increased θ at the beginning of the monsoon, whereas GEP increased more gradually (Figure 2), which reflect differences in the timing of ecosystem responses to rainfall pulses [56].…”
Section: Moisture and Photosynthesis Terms Improve Modeled Carbon-watmentioning
confidence: 99%
“…A final aspect of temporal variability revolves around "hot spots" and "hot moments" in space and time (Leon et al, 2014). These localized and/or short bursts of CO 2 and other greenhouse gases (Kim et al, 2012) affect sampling priorities (Bond-Lamberty et al, 2016) but also provide insight into the degree to which these fluxes are driven by soil microbes or via plant roots (Jarvis et al, 2007;Smith et al, 2017;Vargas et al, 2018). Such dynamics have implications for how microbial processes might be appropriately represented in microbially explicit soil biogeochemical models (Bradford et al, 2019), as microbial activity depends on both the "hospitability" of the environment and the microbial community composition (Wieder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%